2014
DOI: 10.1158/0008-5472.can-14-1408
|View full text |Cite
|
Sign up to set email alerts
|

Host Deficiency in Caveolin-2 Inhibits Lung Carcinoma Tumor Growth by Impairing Tumor Angiogenesis

Abstract: Caveolin-2 (Cav-2), a member of caveolin protein family is largely different from better known caveolin-1 (Cav-1) and thus might play distinct functions. Here, we provide the first genetic evidence suggesting that host-expressed Cav-2 promotes subcutaneous tumor growth and tumor-induced neovascularization using two independent syngeneic mouse models. Host deficiency in Cav-2 resulted in defective and reduced growth of subcutaneously implanted Lewis lung carcinoma (LLC) and B16-F10 melanoma tumors, respectively… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 44 publications
(42 reference statements)
3
19
0
Order By: Relevance
“…The absence of Cav2 protein following genetic deletion (29) provides a positive control, consistent with earlier studies of Cav2 Ϫ/Ϫ mice generated independently (37). The present data are also consistent with Cav2 Ϫ/Ϫ offspring being viable and exhibiting postnatal growth and body mass not different from WT mice (37,40).…”
Section: Caveolin Protein Expressionsupporting
confidence: 92%
See 2 more Smart Citations
“…The absence of Cav2 protein following genetic deletion (29) provides a positive control, consistent with earlier studies of Cav2 Ϫ/Ϫ mice generated independently (37). The present data are also consistent with Cav2 Ϫ/Ϫ offspring being viable and exhibiting postnatal growth and body mass not different from WT mice (37,40).…”
Section: Caveolin Protein Expressionsupporting
confidence: 92%
“…Whereas integral roles have been identified for Cav1 in the vasculature and Cav3 in skeletal muscle, less is known about the physiological role of Cav2. Only 38% of the amino acid sequence between Cav1 and Cav2 is identical, suggesting different functional roles for respective protein isoforms (29,46). In mice, genetic deletion of Cav2 resulted in hypercellularity of the lung parenchyma, where thickened alveolar septa was associated with exercise intolerance attributed to impaired pulmonary gas exchange (37).…”
Section: In Skeletal Muscle Of Mice Lacking Caveolin-2 (Cav2mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably our results also support a pro-tumorigenic and pro-metastatic activity of ADAMTS1, and we provided for the first time the finding that ADAMTS1 originated in the stroma contributes more significantly than ADAMTS1 derived from tumor cells. The use of a syngeneic model with genetically-modified animals has been described for a variety of extracellular molecules [3742]. In this study we added the manipulation of our gene of interest in the implanted tumor cells, revealing its minor contribution, at least in this tumor model.…”
Section: Discussionmentioning
confidence: 99%
“…In our recent paper using newly developed Cav-2 KO mice we have examined the role of host-expressed Cav-2 in regulating tumor growth and tumor growth-induced angiogenesis using subcutaneously implanted Lewis lung carcinoma (LLC) and B16-F10 melanoma cells as the two independent syngeneic mouse models [16] . Our results showed that LLC tumors implanted into Cav-2 KO mice displayed a defective growth and ultimately regressed, which was in a striking contrast to wild type (WT) mice in which LLC tumors displayed a continuous growth.…”
mentioning
confidence: 99%